Analisis Studi Kelayakan Bisnis pada Inovasi Pengembangan Produk Gantungan Baju Plastik Multifungsi - Salwa Zahirah Salsabillah (Universitas Teuku Umar, 2021)
AbstractA clothes hanger is an indispensable tool for hanging clothes when drying, hanging clothes in the closet, bathroom and so on. As the name implies, a clothes hanger can only be hung one shirt. Therefore, researchers developed plastic clothes hanger products by changing the design to add to the functional aspects of the product. However, innovating a product is not easy and has high risks, such as the product's ability to compete with competitors and the need for investment costs that must be taken into account. This study aims to test the business feasibility aspects of Multifunctional Plastic Clothes Hangers by conducting a business feasibility study. Beginning with conducting interviews in the form of a questionnaire given to respondents about the level of interest in multifunctional clothes hanger products, followed by data processing to test aspects of business feasibility. After conducting a feasibility study analysis with 7 financial aspects, all the test results are feasible and the multifunctional plastic coat hanger business is feasible to be realized. Keywords: clothes hanger, multifunctional, development, business, feasibility aspects.